Diagnosis of Odontogenic Sinusitis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Odontogenic sinusitis is an inflammation of the mucous membrane of the maxillary sinus, resulting from the spread of the pathological process from the main source of infection located in the upper jaw. The main manifestation of the disease is a clear headache, which increases when the head is bent, purulent or serous nasal discharge, lacrimation and intoxication syndrome. Diagnosis is based on the collection of anamnestic data, general examination, rhinoscopy, sinus puncture and radiation imaging methods. Treatment includes antibiotic therapy, washing with antiseptics, surgical sanitation of the sinus cavity and the main lesion.